Crafting identities Artisan culture in London, c. 1550-1640 - Kilburn-Toppin, Jasmine (Manchester University Press, 2021)
Crafting identities explores artisanal identity and culture in early modern London. It demonstrates that the social, intellectual and political status of London's crafts and craftsmen were embedded in particular material and spatial contexts. Through examination of a wide range of manuscript, visual and material culture sources, the book investigates for the first time how London's artisans physically shaped the built environment of the city and how the experience of negotiating urban spaces impacted directly on their distinctive individual and collective identities. Applying an innovative and interdisciplinary methodology to the examination of artisanal cultures, the book engages with the fields of social and cultural history and the histories of art, design and architecture. It will appeal to scholars of early modern social, cultural and urban history, as well as those interested in design and architectural history.
Keywords: Artisans -- England -- London -- Social conditions -- 17th century.; Artisans -- England -- London -- Social conditions -- 16th century.; Artisans -- England -- London -- History -- 17th century.; Artisans -- England -- London -- History -- 16th century.; Artisans -- Angleterre -- Londres -- Conditions sociales -- 17e siècle.; Artisans -- Angleterre -- Londres -- Conditions sociales -- 16e siècle.; Artisans -- Angleterre -- Londres -- Histoire -- 17e siècle.; Artisans -- Angleterre -- Londres -- Histoire -- 16e siècle.; DESIGN / History & Criticism.; Artisans -- Social conditions; Artisans; England -- London; 1500-1699; History